1994
DOI: 10.1177/002221949402700805
|View full text |Cite
|
Sign up to set email alerts
|

Homework Practices of General Education Teachers

Abstract: The purpose of this study was to survey the homework practices of general education teachers who teach students with disabilities. A national sample of 441 elementary, middle, and senior high teachers were asked about their homework practices, including their use of adaptations for students with disabilities. The results highlight homework practices and adaptations that are used frequently and perceived by teachers as helpful for students with disabilities. Also discussed are the differences in practices and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 11 publications
0
24
0
6
Order By: Relevance
“…The majority of the studies, however, made use of closed-answer formats (e.g., 30e60 min, 60e90 min; cf. Cooper et al, 1998;Keith & Benson, 1992;Polloway, Epstein, Bursuck, & Jayanthi, 1994).…”
Section: Methods Of Data Collectionmentioning
confidence: 99%
“…The majority of the studies, however, made use of closed-answer formats (e.g., 30e60 min, 60e90 min; cf. Cooper et al, 1998;Keith & Benson, 1992;Polloway, Epstein, Bursuck, & Jayanthi, 1994).…”
Section: Methods Of Data Collectionmentioning
confidence: 99%
“…A subsequent study investigated actual classroom practices through a nationwide survey of 441 general education teachers (Polloway, Epstein, Bursuck, Jayanthi, & Cumblad, 1994). The high frequency and timeintensive nature of regular homework cited above was confirmed.…”
Section: Homework Problems Of Children With Disabilitiesmentioning
confidence: 84%
“…In a finding relevant to the issue of home-school communication, Polloway et al (1994) found that secondary teachers were likely to give the most homework, but tended to place a somewhat lower value on home-school communication. Indeed, a number of strategies, such as sending notes home, were perceived as too extensive in terms of time, effort, and=or direct contact.…”
Section: Home-school Communication Patternsmentioning
confidence: 99%
“…We asked the students how many hours they invest at home working for school per an average school week using a closed-answer format (less than one hour, 1-3 hours, 3-5 hours, 5-10 hours, more than 10 hours; cp. Cooper, Lindsay, Nye, & Greathouse, 1998;Keith & Benson, 1992;Polloway, Epstein, Bursuck, & Jayanthi, 1994). All other scales including examples of items and Cronbachs' Alphas are shown in table 1.…”
Section: Methodsmentioning
confidence: 99%